Mitigation of delay in industrial construction projects; case of Iran - Ebrahimzadeh Sepasgozar, Samad Mohammad (2008)

(untitled)
Delays are one of the biggest problems construction firms face. It happens in most construction projects. Delays can lead to many negative effects such as lawsuits between owners and contractors, increased costs, loss of productivity and revenue, and contract termination. According to Bordoli and Baldwin (1998) and the World Bank (1990), for 1627 projects completed worldwide between 1974 and 1988, the overrun varied between 50% and 80%. In the United Arab Emirates, where construction contributes 14% to the gross domestic product, a study by Faridi and El-Sayegh (2006) revealed that 50% of construction projects encounter delays. In Iran many of constriction projects encounter delays also. This paper addresses two primary research questions as how do often happen delay in industrial construction projects? And how can a contractor mitigate of project delays? To achieve the above research questions, a case study approach will use in this research. The case study is selected in Iran. Data is collected through interviews and project documents.